SCIENTIFIC-THEORETICAL-METHODOLOGICAL BASES OF THE USE OF MODERN PEDAGOGICAL TECHNOLOGIES IN EDUCATION (American Journal of Pedagogical and Educational Research, 2025)
The scientific-theoretical-scientific basis for the use of modern pedagogical technologies in education, information and communication technologies (ICT), modern pedagogical technologies in education, the introduction of modern pedagogical technologies in education creates unique opportunities, and a number of problems are discussed.